Economics of small-scale forest carbon projects in South Sumatra, Indonesia - Guillermo, I.A. (University of the Philippines, 2004)
The Clean Development Mechanism provides opportunities for land rehabilitation of degraded lands through afforestation and reforestation project activities in the effort to mitigate climate change. This study was conducted in a Pulai (Alstonia) plantation developed by PT. Xylo Indah Pratama, in South Sumatra, Indonesia, in partnership with more than 1,749 smallholders of private lands. The actual costs incurred in plantation development were used to estimate the potential cost of forest carbon projects in the same area. The existing plantation is not eligible as a sink project under the current rules of the CDM. However, results show potential for new groups of smallholders to be eligible. Under the same rules mentioned, a project with a size of 104 ha to 250 ha would cost $3,121/ha to $1,254/ha respectively, and can produce 130 tC (476 tCERs) after a 10-year crediting period. In order to attract farmers/smallholders of land in Musi Rawis to plant trees to help in climate change mitigation in small-scale, carbon must be sold at $62/t. The project will still be feasible, or be able to absorb the huge amount of fixed costs, at the minimum size of 104 ha. The cost of production per ha of a 10,000-ha project is $571 with a unit cost of $3.98/tC. The suitable market price is $17/tC to attract farmers to plant trees for climate change mitigation purposes if operated on a large-scale. The results further imply that if C is bought at the current market price of $10/tC, forest carbon projects will not be able to compete with other land-uses that provide better socio-economic benefits. Therefore, credits earned by low-income communities in particular should be considered as “additional incentive”.